Blood cultures for the diagnosis of multidrug-resistant and extensively drug-resistant tuberculosis among HIV-infected patients from rural South Africa: a cross-sectional study. - Heysell, Scott K; Thomas, Tania A; Gandhi, Neel R; Moll, Anthony P; Eksteen, François J; Coovadia, Yacoob; Roux, Lynette; Babaria, Palav; Lalloo, Umesh; Friedland, Gerald; Shah, Sarita (BMC infectious diseases, 2010)
The yield of mycobacterial blood cultures for multidrug-resistant (MDR) and extensively drug-resistant tuberculosis (XDR-TB) among drug-resistant TB suspects has not been described.
Keywords: Adolescent; Adult; AIDS-Related Opportunistic Infections; Child; Child, Preschool; Cross-Sectional Studies; Extensively Drug-Resistant Tuberculosis; Female; HIV Infections; Humans; Infant; Infant, Newborn; Male; Middle Aged; Mycobacterium tuberculosis; Retrospective Studies; Risk Factors; Rural Population; South Africa; Sputum; Young Adult